2016
DOI: 10.1021/acs.jpcc.5b12293
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability of Rubrene against Oxidation by Partial and Complete Fluorination

Abstract: We report on the oxidation potential of partially fluorinated (C42F14H14, F14-RUB) and perfluorinated rubrene (C42F28, PF-RUB) studied by cyclic voltammetry (CV) in solution as well as by spectroscopic ellipsometry and near edge X-ray absorption fine structure (NEXAFS) spectroscopy in thin films in combination with density functional theory computations. Due to their different electronic structure, the fluorinated derivatives have a higher oxidation potential and are more stable than rubrene (C42H28, RUB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…In practice, best‐performing semiconductors in OFETs tend to have IP s ranging from 5.1–5.3 eV because it is a good compromise between easy charge injection and stability versus oxidation . Compounds with IP < 5.1 eV tend to oxidize easily and their transport properties can be subject to oxygen doping . The difference between the ionization potential in solid state ( IP s ) minus the one obtained in gas phase ( IP g ) affords the polarization energy P + that evidently depends on the packing motif P+=IPsIPg…”
Section: Charge Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, best‐performing semiconductors in OFETs tend to have IP s ranging from 5.1–5.3 eV because it is a good compromise between easy charge injection and stability versus oxidation . Compounds with IP < 5.1 eV tend to oxidize easily and their transport properties can be subject to oxygen doping . The difference between the ionization potential in solid state ( IP s ) minus the one obtained in gas phase ( IP g ) affords the polarization energy P + that evidently depends on the packing motif P+=IPsIPg…”
Section: Charge Transportmentioning
confidence: 99%
“…One new research line would then consist in growing single crystals of pure organic semiconductors with well distributed dopant molecules that are commensurate with the crystal lattice of known molecular semiconductors. For example, one can imagine alloying rubrene 3 with the recently reported perfluororubrene provided that the latter can fit within the crystal lattice of the former and is a sufficiently good acceptor . The situation is, thus, different from the cocrystallization of donor and acceptor systems forming crystal structures that have nothing in common with those of pure components.…”
Section: Charge Transportmentioning
confidence: 99%
“…The results revealed that a native crystalline rubrene peroxide layer is formed on top of crystalline domains of pristine rubrene . One strategy to enhance the stability of rubrene is a chemical modification of the rubrene core via fluorination . Anger et al demonstrated that modification of rubrene with fluorine atoms could enhance the stability of rubrene against photo‐oxidation both in solution and in the solid state because of the increased oxidation potential …”
Section: Approaches To Overcome the Instability Caused By Degradationmentioning
confidence: 99%
“…88, 103901 (2017) in the context of solvent annealing microstructural transformations, 29 organic semiconductor (OSC)-based sensors, 30 and OPV stability. 31 One frequently used molecule is bathophenanthroline (BPhen), which is typically used as a buffer or doped electron transport layer between the active layer organic absorber/emitter and the evaporated metal cathode, composed of materials such as aluminium. Although ubiquitous in a number of organic light emitting diode (OLED) and OPV architectures, few if any investigations of the microstructure of vacuum-deposited BPhen exist.…”
Section: -6mentioning
confidence: 99%